2010
DOI: 10.1177/1368430210369680
|View full text |Cite
|
Sign up to set email alerts
|

Refining the relationship between ingroup identification and identity management strategies in the sport context: The moderating role of gender and the mediating role of negative mood

Abstract: The aim of this exploratory research was to refine the relationship between ingroup identification and three classical identity-management strategies: individual mobility, social competition and social creativity. More specifically, in the particular context of sport spectators' reactions to their team loss, we tested the moderating role of gender in differentiating the use of CORFing (distancing) strategy and the mediating role of negative mood in differentiating the use of social competition and social creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 50 publications
2
12
0
Order By: Relevance
“…This belief enabled respondents to maintain a positive team identity by legitimising and enhancing their status in the group (Wann & Branscombe, 1990). Our findings[ 1 0 _ T D $ D I F F ] build on previous quantitative work that revealed a statistical correlation between identification and future performance expectations of a recently defeated rugby team (Bernache-Assollant et al, 2010). We contribute qualitative insights, which indicate that supporters make sense of their team identification using current and future frames of reference.…”
Section: Through This Research We Have Contributed To Understanding supporting
confidence: 63%
See 1 more Smart Citation
“…This belief enabled respondents to maintain a positive team identity by legitimising and enhancing their status in the group (Wann & Branscombe, 1990). Our findings[ 1 0 _ T D $ D I F F ] build on previous quantitative work that revealed a statistical correlation between identification and future performance expectations of a recently defeated rugby team (Bernache-Assollant et al, 2010). We contribute qualitative insights, which indicate that supporters make sense of their team identification using current and future frames of reference.…”
Section: Through This Research We Have Contributed To Understanding supporting
confidence: 63%
“…Ken's and Justine's statements outline a use of social creativity in preserving in-group status by boosting the team's future prospects immediately after poor performances, supporting existing work (e.g., Bernache-Assollant et al, 2010).…”
Section: Framing the Futurementioning
confidence: 99%
“…This work shows that when the in-group is not able to fulfi l the group members' need for positive collective self-esteem, group members who do not feel a strong attachment with their group (i.e. low group identifi cation) tend to leave the group (Bernache-Assollant, Laurin, Bouchet, Bodet, & Lacassagne, 2010 ;Cadinu & Cerchioni, 2001 ;Ellemers, Spears, & Doosje, 1997 ;Jetten, Iyer, Tsivrikos, & Young, 2008 ). For example, Ellemers et al ( 1997 , Study 1) indicated that threatened low identifi ers more strongly desired individual mobility compared to high identifi ers, independent of the permeability of the group boundaries.…”
Section: Expanding the Self-esteem Hypothesis To Other Identity Managmentioning
confidence: 96%
“…Results revealed that female fans tended to be more highly identified than male fans [Ms = 6.39 vs 5.85 for women and men, respectively; F(1, 92) = 2.86, p = .094, η p ² = .03]. Consequently, and because past research suggests that gender constitutes a salient basis for categorization in the sport spectatorship context (see e.g., Bernache-Assollant, Laurin, Bouchet, Bodet, & Lacassagne, 2010), further analyses included gender as a grouping variable.…”
Section: Preliminary Analysesmentioning
confidence: 93%